2021
DOI: 10.1155/2021/7722269
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association between Triglyceride-Rich Lipoprotein Cholesterol and Diabetes Mellitus in Hypertensive Patients

Abstract: Background. The association between triglyceride-rich lipoprotein cholesterol (TRL-C) and diabetes mellitus (DM) remains unclear because of limited research and data. The aim of this study was to explore the independent association between TRL-C and DM in hypertensive patients and to examine whether a healthy lifestyle would have an impact on this relationship. Methods. In this study, data from 13,721 hypertensive patients who were not treated with lipid-lowering drugs were analyzed. TRL-C was calculated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…The present study also found that RC and diabetes remained strongly associated regardless of whether the participant was overweight or not. Zhou et al 21 found a positive correlation between RC and diabetes in 13 721 hypertensive patients; however, RC and diabetes were associated only in persons with normal blood pressure in the current investigation. We speculate that this is because the number of hypertension patients in the current research was modest in comparison to Zhou's team's investigation.…”
Section: Stratification Analysiscontrasting
confidence: 75%
See 1 more Smart Citation
“…The present study also found that RC and diabetes remained strongly associated regardless of whether the participant was overweight or not. Zhou et al 21 found a positive correlation between RC and diabetes in 13 721 hypertensive patients; however, RC and diabetes were associated only in persons with normal blood pressure in the current investigation. We speculate that this is because the number of hypertension patients in the current research was modest in comparison to Zhou's team's investigation.…”
Section: Stratification Analysiscontrasting
confidence: 75%
“…Szili‐Torok et al 20 analyzed 480 patients who had undergone kidney transplantation, and they found a significant association between RC and new‐onset diabetes after kidney transplantation. Zhou et al 21 found a positive correlation between RC and diabetes in 13 721 Chinese hypertensive patients. Nevertheless, the current study population was the large sample general Chinese population, including subjects with various chronic diseases and healthy subjects; hence, the findings of the current study were more generally applicable.…”
Section: Discussionmentioning
confidence: 97%
“…In the Cox model with adjusted basic covariates, TRL-c significantly correlated with diabetes (HR = 1.39, 95% CI 1.28–1.51, P < 0.001). Zhou Wei et al [ 9 ] in China conducted a cross-sectional analysis of the data of 13,721 hypertensive patients without lipid-lowering drugs. They found that TRL-c significantly and positively correlated with diabetes risk (OR = 1.73, 95% CI: 1.54–1.94).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a positive correlation between TRL-c and diabetes has been investigated in recently published studies [ 8 , 9 ]. However, the results obtained from another study suggested no correlation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%